ANALISIS KEMAMPUAN HEADING SEPAK BOLA SISWA KELAS V SEKOLAH DASAR NEGERI 276/VI AIR BATU II KECAMATAN TABIR ILIR KABUPATEN MERANGIN - DEKA ISMI MORI SAPUTRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT This research was motivated by the problems related to the learning outcomes of headings that are not optimal yet. the practice score was low (the minimum score). It was caused by performing of the heading technique that showed both shoulders of students are flat, the body position was not in the direction of the ball as required to perform the correct heading technique. This study aimed to determine the level of heading technique ability for fifth grade students of SD 276/VI Merangin.This research was quantitative descriptive research. The purpose of this research was to describe how to analyze the Heading technique error. The sample in this research was the fifth grade students of SD 276/VI Merangin. The total sample was 16 students. The instrument of this research used a test of playing the ball by using head. The data analysis technique used descriptive and quantitative in the form of percentages.Based on the results of the research, it can be concluded that the skill of playing the ball by using head of the fifth grade students of SD 276/VI Air Batu II, Tabir Ilir District, Merangin Regency was sufficient. The percentage of the results was 6.25% of students in very good category; 25.00% of students in good category; 25.00% of students in the moderate category; 43.75% of students in the poor category; and 0% of student in the very poor category. Keywords: Analysis, Heading, Football